Study of silver azide explosive decomposition by spectroscopicmethods with high temporal resolution; Solid State lonics; Vol. 101-103, Part 1 - Aduev B. P.; Aluker E. D.; Kriger V. G.; Zakharov Yu. A. Yuriy Aleksandrovich (1997, 1997)
Title screen